1983
DOI: 10.1161/01.hyp.5.4.539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of withdrawing diuretic therapy on blood pressure in mild hypertension.

Abstract: SUMMARY A 1-year double-blind placebo-controlled study on the effects of diuretic withdrawal was conducted on a group of 62 previously well-controlled, mildly hypertensive patients. Data were collected on blood pressure (BP), biochemical laboratory values, and subjective reports of side-effects. Twenty-six percent of placebo subjects and 3% of the active treatment subjects reached preset criteria for the return of hypertension (reverters). The average systolic and diastolic pressures of all placebotreated pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Later, discontinuation of treatment was reinvestigated in patients who completed the randomized trials of mild hypertension. On the basis of reports of the Medical Research Council trial [19] and the Hypertension Detection and Follow-up Program (HDFP) trial [20] and a few smaller trials [21,22], the following conclusions can be drawn: patients with milder hypertension at entry are more likely to stay normotensive; a substantial proportion of patients remain normotensive or near normotensive for 1 year or more; and in patients whose blood pressure will rebound, the return of hypertension is brisk and likely to be seen in the first 4 months after discontinuation of treatment. The percentage of patients who remain normotensive depends on the definition of normal blood pressure, but it ranges from 50% to 75% at 1 year and from 45% to 52% after 2 years.…”
Section: Prolonged Normotension After Discontinuation Of Antihypertenmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, discontinuation of treatment was reinvestigated in patients who completed the randomized trials of mild hypertension. On the basis of reports of the Medical Research Council trial [19] and the Hypertension Detection and Follow-up Program (HDFP) trial [20] and a few smaller trials [21,22], the following conclusions can be drawn: patients with milder hypertension at entry are more likely to stay normotensive; a substantial proportion of patients remain normotensive or near normotensive for 1 year or more; and in patients whose blood pressure will rebound, the return of hypertension is brisk and likely to be seen in the first 4 months after discontinuation of treatment. The percentage of patients who remain normotensive depends on the definition of normal blood pressure, but it ranges from 50% to 75% at 1 year and from 45% to 52% after 2 years.…”
Section: Prolonged Normotension After Discontinuation Of Antihypertenmentioning
confidence: 99%
“…All patients in the trial will receive literature on diet and exercise throughout the study. Patients will be evaluated at 3,6,9,12,15,18,21, and 24 months for the 2-year double-blind treatment period. To ensure compliance and allow patients to monitor blood pressure between visits, patients will be provided with the OMRON 705-CP device (OMRON Healthcare, Inc. Vernon Hills, IL) for home blood pressure measurements.…”
Section: Trophy Study Descriptionmentioning
confidence: 99%
“…Although the mechanism of the sustained antihypertensive effect observed over several weeks following the cessation of intake is unclear, previous studies have shown similar results. [31][32][33] In several ACE inhibitory substances, the slow absorption and the inhibition of the tissue renin-angiotensin system were reported in human or animal studies. 29,34,35 Peptide composition of A. oryzae casein hydrolysate was reported to mainly comprise small peptides, X-Pro-Pro and X-Pro.…”
mentioning
confidence: 99%
“…Most study groups have observed that a subset of formerly treated hyperten sive patients remained normotensive after drug with drawal [14][15][16][17][18][19][20], In those studies, the proportion of pa tients showing remission of hypertension ranged from 10 to 75%; however, follow-up was limited to 4 years or less. Overall, the percentage of patients remaining normoten sive after drug withdrawal decreases over time.…”
Section: Discussionmentioning
confidence: 99%